Non-enzymatic properties of Proteus mirabilis urease subunits. (November 2021) - Broll, Valquiria; Perin, Ana Paula A.; Lopes, Fernanda C.; Martinelli, Anne Helene S.; Moyetta, Natalia R.; Fruttero, Leonardo L.; Grahl, Matheus V.C.; Uberti, Augusto F.; Demartini, Diogo R.; Ligabue-Braun, Rodrigo; Carlini, Celia R.
Graphical abstract: Highlights: Proteus mirabilis oligomeric urease is a moonlighting virulence factor. Holo-urease promoted platelet aggregation and toxicity in fungal and insect models. Subunit Ureβ has the highest toxicity while also activating platelets. Bioinformatics analyses revealed gene/segment duplication. Ureβ and its counterparts in other ureases carry most of the non-enzymatic activities. Abstract: Ureases are moonlighting proteins displaying non-catalytic properties, including platelet activation, antifungal and entomotoxic effects. The structure-activity mapping of these properties is poorly developed. Proteus mirabilis urease (PMU) consists of three subunits, PmUreα, PmUreβ and PmUreγ, in an (αβγ)3 organization. In order to study the structure-activity relationships of PMU we obtained the recombinant subunits of this urease and evaluated their biological activities. The holo-urease promoted platelet aggregation, and toxicity in fungal and insect models. Similar to Jaburetox, a plant urease-derived polypeptide, PmUreβ showed the highest toxicity against yeasts and insects, and activated human platelets. PmUreγ and PmUreα presented insecticidal action upon injection. In addition, only PmUreγ and PmUreβ promote hemocytes aggregation. Bioinformatics analyses revealed gene/segment duplication and evolutionary divergence among ureases. Our findings show that PmUreβ (and probably its counterparts in other ureases) carries most of the non-enzymatic activities of these proteins.